Planar and 3D interdigitated electrodes for biosensing applications: The impact of a dielectric barrier on the sensor properties. Issue 6 (2nd April 2014) - Bäcker, M.; Kramer, F.; Huck, C.; Poghossian, A.; Bratov, A.; Abramova, N.; Schöning, M. J.
<x xml:space="preserve">Abstract</x> Planar and three‐dimensional (3D) interdigitated electrodes (IDE) with electrode digits separated by an insulating barrier of different heights were electrochemically characterized and compared in terms of their sensing properties. Due to the impact of the surface resistance, both types of IDE structures display a non‐linear behavior in low‐ionic strength solutions. The experimental data were fitted to an electrical equivalent circuit and interpreted taking into account the surface‐charge‐governed properties. The effect of a charged polyelectrolyte layer electrostatically assembled onto the sensor surface on the surface resistance in solutions with different KCl concentration is studied. In case of the same electrode footprint, 3D‐IDEs show a larger cell constant and a higher sensitivity to molecular adsorption than that of planar IDEs. The obtained results demonstrate the potential of 3D‐IDEs as a new transducer structure for a direct label‐free sensing of charged molecules.